Dentro de los límites de lo visible: el fuera de campo del cine chileno posdictatorial - Barraza, Vania (2025)
This article examines the limited representation of violence in Chilean productions from the early 21st century, as a reflection of the democracy of agreements promoted by the “Concertación” governments (1990–2010). The analysis focuses on how violence is often displaced off-screen in the works of three directors from different generations: Andrés Wood, Miguel Littin, and Pablo Larraín. From the films of these directors, two trends in representation are identified: one reproduces a consensual perspective on historical events, while the other aims to challenge the democracy of agreements by introducing new subjectivities into Chilean historical cinema.